Identification of Fusarium oxysporum f.sp cepae race 4 isolated from shallots in East Java Indonesia - Moch Nur Yudha; Sri Wiyatiningsih; Tri Mujoko (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Fusarium oxysporum f.sp cepae (Foce) which causes moler disease, has been mutated into four races. The fourth race is the riskiest due to its vulnerability to being attacked by various cultivars. This research aims to identify the existence of Foce Race 4 in the shallot production center districts. The plant samples attacked by moler disease were taken in three districts (i.e., Magetan, Nganjuk, and Probolinggo) by Purposive Random Sampling method with 5% samples, obtaining 9 Foce isolates. The results were then identified using Volatile Odor Test (VOT), Biochemistry, and Vegetative Compatibility Group (VCG); four were identified as Race 4. Those four isolates were then examined for their virulences towards three cultivars, particularly Bauji, Tajuk, and Biru Lancor. The findings show that all four isolates were noxious and able to plague all the varieties.